FRAMING HEALTH IN PRESIDENTIAL DISCOURSE: A COMPARATIVE COGNITIVE STUDY OF THE U.S. AND UZBEKISTAN DURING COVID-19 (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article presents a comparative cognitive analysis of the concept of health in American and Uzbek presidential discourse during the COVID-19 pandemic. Based on speeches by Donald Trump, Joe Biden, and Shavkat Mirziyoyev, the study applies cognitive linguistics, conceptual metaphor theory, and discourse analysis. The findings show both similarities and cultural differences: American discourse frames health through war, individual responsibility, and national security, while Uzbek discourse emphasizes health as a collective social value and moral responsibility. The study highlights the role of cultural and cognitive models in shaping political representations of health.